Understanding the Perspectives of Small-Scale Arable Crop Farmers on Soil Management Practices in Uhen L.G.A, Edo State (American Journal of Multidisciplinary Research and Innovation, 2024)
This study provides insights into the perceptions of small-scale arable crop farmers in Uhen L.G.A regarding soil management practices. A total of 50 questionnaires were administered to randomly selected farmers and the questionnaires covered various aspects, including demographics, farming and soil fertility management practices, awareness of organic agriculture, soil health, and soil fertility, as well as acceptance, viability, and sustainability of organic inputs. The findings revealed that the majority of the respondents were male, with a range of ages and educational backgrounds, mostly attaining secondary education with varying levels of farming and agricultural experience. Regarding farming and soil fertility management practices, respondents reported adopting practices such as tillage, mound/heaps/ridges, bush burning, mulching, and mixed cropping. Organic fertilization was more commonly used than inorganic fertilization, with reasons cited including availability, low cost, crop response, and long-term effects. Farmers recognized the importance of organic residue and soil organisms for soil health. However, there was limited awareness of organic agriculture among the respondents, and their knowledge of soil organisms and their contributions to soil health was moderate. The findings highlight the need for increased awareness and knowledge of organic agriculture and the potential benefits of organic inputs for soil health and fertility.